JURIDICAL ANALYSIS OF E-CONSENT SERVICES BASED ON LAW NUMBER 17 OF 2023 ON HEALTH AT ZAINAL ABIDIN HOSPITAL, PAGAR ALAM, WAY KANAN - Mahaputra, Muhd. Hamka; Septiana, Dewi; Kh K, A Rahman; Atasever, Yaşar Nuri (Sriwijaya Crimen and Legal Studies, 2024)
The“development of information technology in the health sector has significantly changed how health services are delivered and regulated. One important change is the shift from conventional informed consent (oral or written) to e-consent or electronic technology-based consent. According to Article 335 of Law No. 17 Year 2023 on Health. Informed consent is a key element in ethical and legal medical practice. The main principle is the individual must give that consent. Based on Article 2 paragraph (1) Permenkes RI Number 290 /Menkes / Per / III / 2008 concerning Medical Action Consent states that “All actions that will be carried out on patients must obtain consent”, therefore the article aims to analyze the rules for implementing e-consent and the obstacles to the application of e-consent in health services, especially at the Hospital Rsud Zainal Abidin Pagar Alam Way Kanan. This research method uses normative Judicial legal research. The results showed that the rules for e-consent have been regulated in Indonesian legislation, but the use of e-consent has weaknesses, such as patients, doctors, and other medical personnel not being accustomed to changes from conventional to digitalization. In addition, inadequate equipment from the Hospital is also an obstacle to implementing this E-consent service.”The proposed suggestion is the need for improvement and training regarding the rules and work practice training related to e-consent between doctors, medical personnel, and patients at Zainal Pagar Alam Way Kanan Hospital.